At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
- y = 6
Step-by-step explanation:
Use the second equation:
- 2x - y = 2 ⇒ y = 2x - 2
Substitute this into first equation:
- 3x + 4(2x - 2) = 36
- 3x + 8x - 8 = 36
- 11x = 44
- x = 4
Now find y:
- y = 2*4 - 2
- y = 8 - 2
- y = 6
It is given that,
→ 2x - y = 2
Convert the equation as,
→ y = 2x - 2
First we should,
find the required value of x.
→ 3x + 4(2x - 2) = 36
→ 3x + 8x - 8 = 36
→ 11x = 44
→ [x = 4]
Let's find the required value of y,
→ y = 2x - 2
→ y = (2 × 4) - 2
→ y = 8 - 2
→ [y = 6]
Therefore, the value of y is 6.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.